Safety, accessibility, comfort:gender audit of urban space in Kyiv - Коцюба, Ярослав; Провотар, Наталія Іванівна (Київський національний університет імені Тараса Шевченка, 2025)
Background. Cities are spaces of intensive social, economic, and political interactions, where spatial decisions and urban planning practices have unequal consequences for different social groups of residents. A gender audit in urban space is considered a practical methodology that allows for the systematic assessment of how policies, spatial practices, and infrastructure take into account or ignore the needs of people of different genders. It provides a basis for developing corrective measures and policies aimed at reducing gender barriers in access to urban spaces and urban resources. Methods. The study employs the methods of observation, in-depth semi-structured interviews, the semantic differential method, analysis and synthesis, and the graphical method. Results. The article presents an assessment of urban space in terms of its safety, accessibility, and comfort from a gender perspective, using two case studies in the city of Kyiv – residential complexes of business and economy class. The findings show that women associate comfort with coziness, well-maintained spaces, lighting, and safety, while men tend to focus more on practicality, functionality, and access control. Women’s evaluations are more oriented toward everyday comfort, a sense of safety, and child- and family-related needs, whereas men demonstrate a rational approach with a generally positive overall assessment. The responses of women and men create a complementary picture: women emphasize "how one feels in a space," while men focus on "how it can be organized technically." Conclusions. The absence of a gender-sensitive approach in urban planning leads to inequalities in mobility, increases the vulnerability of certain groups, and limits their participation in urban life. Currently, Ukraine lacks national building standards for gender-sensitive urbanism; therefore, cities that are convenient for everyone are planned with consideration of such requirements as safety, accessibility, walkability, and comfort.

Вступ. Міста є простором інтенсивних соціально-економічних та політичних взаємодій, у яких просторові рішення та практики міського планування мають неоднакові наслідки для різних соціальних груп мешканців. Гендерний аудит у міському просторі розглядається як практична методика, що дає змогу систематично оцінити, яким чином політики, просторові практики та інфраструктура враховують чи ігнорують потреби людей різних статей. Він дає підстави для розробки коригувальних заходів та політик, що спрямовані на зниження гендерних бар’єрів у доступі до міського простору та міських благ. Методи. У дослідженні використано метод спостережень, глибинних напівструктурованих інтерв'ю, метод семантичного диференціалу, аналіз і синтез, графічний метод. Результати. Здійснено оцінку міського простору на предмет його безпеки, доступності та комфортності за гендерною ознакою на прикладі двох кейсів у місті Києві: житлових комплексів бізнес- та економкласу. Виявлено, що жінки вбачають комфорт у затишку, доглянутому просторі, освітленні й безпеці, тоді як чоловіки більше орієнтуються на практичність, функціональність та контроль доступу. Жінки у своїх оцінках більше орієнтовані на повсякденний комфорт, атмосферу безпеки та дитячо-сімейні потреби, а чоловіки демонструють раціональний підхід з узагальнено-позитивною оцінкою. Відповіді жінок і чоловіків створюють комплементарну картину: жінки акцентують увагу на "як почуваєшся у просторі", чоловіки – "як це організувати технічно". Висновки. Відсутність гендерного підходу у міському плануванні призводить до нерівностей у мобільності, збільшує вразливість певних груп та обмежує їхню участь у міському житті. Нині в Україні відсутні державні будівельні норми з гендерної урбаністики, тому зручні для всіх міста плануються з урахуванням таких вимог, як безпека, безбар’єрність, пішохідна доступність та комфортність.
Безпека, доступність, комфортність: гендерний аудит міського простору Києва
Beebeejaun, Y. (2016). Gender, urban space, and the right to everyday life. Journal of Urban Affairs, 39(3), 323–334. https://doi.org/10.1080/07352166.2016.1255526 Fawcett, G. (2023). Gender Audit Guide. New York: United Nations Entity for Gender Equality and the Empowerment of Women. Gender accessibility audit toolkit. (2019). https://eca.unwomen.org/sites/default/files/Field%20Office%20ECA/Attachments/Publications/2019/gender-accessibility-audit-ENG_compressed.pdf Gender best practices in public transport. (2024). https://www.eib.org/attachments/documents/explore-gender-best-practices-in-public-transport.pdf Gender Equality Action Plan 2020–2023. (2020). https://www.ei-ie.org/en/item/25125:gender-equality-action-plan-2020-2023 Gender in development organisations. (1997). https://policy-practice.oxfam.org/resources/gender-in-development-organisations-121450 Gender Mainstreaming: Gender audit. (2019). https://eige.europa.eu/sites/default/files/documents/mh0218737enn_002_0.pdf Gough, A. (2016). The gendered city. Sustainability citizenship in cities: Theory and Practice. In R. Horne, B. Fien, A. Beza, J. Nelson (Еds.). Routledge. https://doi.org/10.4324/9781315678405 Guidelines to mainstream gender in transport projects. (2021). https://openknowledge.worldbank.org/bitstreams/815b1aba-db23-5172-8b47-0210c3a08a9c/download Lewkowitz, S., & Gilliland, J. (2025). A feminist critical analysis of public toilets and gender: A systematic review. Urban Affairs Review, 61(1), 282–309. https://journals.sagepub.com/doi/full/10.1177/10780874241233529 Methodology for conducting a comprehensive gender audit of urban space. (2020) [in Ukrainian]. [Методика проведення комплексного гендерного аудиту міського простору. (2020).] https://www.genderculturecentre.org/wp-content/uploads/2020/11/METHODS-OF-CONDUCTING-A-COMPREHENSIVE-GENDER-AUDIT-SPACE.pdf Pereira, A., & Rebelo, E. M. (2024). Women in public spaces: perceptions and initiatives to promote gender equality. Cities, 154, 105346. https://doi.org/10.1016/j.cities.2024.105346 Podestà, L. (2023). Gender equality in urban planning. A crucial factor for real inclusive development. https://www.diva-portal.org/smash/get/diva2:1764964/FULLTEXT02 Provotar, N., & Kotsiuba, Y. (2024). Lanning cities based on gender equality principles: approaches and experiences. Bulletin of the Taras Shevchenko National University of Kyiv. Geography, 3–4 (90–91), 7–13 [in Ukrainian]. [Провотар Н., & Коцюба Я. (2024). Планування міст на засадах гендерної рівності. Вісник Київського національного університету імені Тараса Шевченка. Географія, 3–4 (90–91), 7–13.] http://doi.org/10.17721/1728-2721.2024.90-91.1 Safe cities and safe public spaces for women and girls global flagship initiative: International compendium of practices. (2019). https://www.unwomen.org/sites/default/files/Headquarters/Attachments/Sections/Library/Publications/2019/Safe-cities-and-safe-public-spaces-Compendium-of-practices-en.pdf Safe cities and safe public spaces global results report 2017–2020. (2021). https://www.unwomen.org/sites/default/files/Headquarters/Attachments/Sections/Library/Publications/2021/Safe-Cities-and-Safe-Public-Spaces-global-results-report-2017-2020-en.pdf Sandström, I., Ericsson, S., & Hedvall, P.-O. (2024). Gendered sustainability: Are public spaces designed for girls good for everyone? Examining female participation as a strategy for inclusive public space. Cities, 149, 104906. https://doi.org/10.1016/j.cities.2024.104906 Tandogan О., & Ilhan В. (2016). Fear of Crime in Public Spaces: From the View of Women Living in Cities. Procedia Engineering, 161, 2011–2018. https://doi.org/10.1016/j.proeng.2016.08.795 Women's safety audits: What works and where? (2013). https://unhabitat.org/sites/default/files/download-manager-files/1404462831wpdm_Women%27s%20Safety%20Audit.pdf Yadav, A., & Kumari, R. (2023). Towards gender-inclusive cities: Prioritizing safety parameters for sustainable urban development through multi-criteria decision analysis. International Journal of Sustainable Building Technology and Urban Development, 14(3), 361–374. https://doi.org/10.22712/susb.20230027 Yadav, A., & Kumari, R. (2024). Gender safety perspective in urban planning: The case of pedestrian mobility in Kanpur city. Cities, 147, 104845. https://doi.org/10.1016/j.cities.2024.104845 Yossa N., Kim, Ch., Pojani, D., & Sipe, N. (2023). Is public transit meeting the needs of women? A gender audit of two Asian metro systems. Journal of Urban Design, 29(4), 318–341. https://www.tandfonline.com/doi/full/10.1080/13574809.2023.2240247
Keywords: city; gender audit; urban space; safety; accessibility; comfort; Kyiv; Ukraine; місто; гендерний аудит; міський простір; безпека; доступність; комфортність; Київ; Україна